Differential toxicity of Pb & Hg on the development of modular traits, photosynthetic and biochemical attributes in two varieties of a forage crop species Trifolium alexandrinum L. - Fatima, Maryam; Mahmood, Seema (International Journal of Biological Research, 2016)
Heavy metal stress as result of natural and anthropogenic activities is main environmental problem. Pb and Hg are among non-biodegradable metals thus remaining persistent in soil and water. The present study was carried out to assess growth and biochemical responses of two varieties (Desi and Misri) of Trifolium alexandrinum L. after application of varying levels (25mg/kg, 50mg/kg and 100mg/kg) of Pb and Hg in soil along with control. Seed germination, biomass of above and below ground tissues, number of flowers and leaves, leaf area and nodulation was observed. For biochemical attributes, green pigments, protein and amino acids, were determined. Both varieties (Desi and Misri) showed variable responses in relation to both Pb and Hg. Similarly, the pattern of character expression was independent for metal levels and types. Misri performed consistently better as it showed best threshold for most of the attributes studied. Hg was found to be more toxic as compared to the Pb as it induced more drastic decline in parameters studied. The study showed that biometric traits can be used as good predictors and the biochemical parameters cannot be used as useful biochemical markers as they showed no marked disparity.